PENDAMPINGAN IBU EARLY POST-PARTUM “CEGAH PP BLUES DENGAN DASS 21” DI BPM LUKLUATUN MUBRIKOH - Selvia Nurul Qomari; Lelly Aprilia Vidayati (STIKES NGUDIA HUSADA MADURA, 2019)
The postpartum period is a time when there are changes in women, both changes in biological conditions, psychological changes and adaptations of a woman. Strees Post Partum is a post partum mother who experiences feelings of sadness or experiences psychological disorders with various syndromes or symptoms (Kasdu, 20030). According to WHO (2012) about 25% -85% of postpartum mothers will experience the blues. Between 7% and 17% have postpartum depression, 0.2% become postpartum psychosis. The incidence of postpartum depression in developing countries occurs with an incidence prevalence of 10-15%. In Indonesia, several studies have been conducted on postpartum depression. Based on research conducted by Rismintari (2012), it was noted that 33% of mothers experienced postpartum depression. Based on the results of the examination, it was found that there were 4 postpartum mothers who experienced anxiety. This is because the primiparous postpartum mothers do not know how to care for babies, the absence of their husbands, and an unsupportive family environment. Assistance participants were 12 postpartum mothers with symptoms of post partum blues at BPM Lukluatun Mubrikoh who were provided with post partum ealy assistance. After several days of mentoring, it was found that some postpartum mothers who were at risk of post-partum blues showed improvement in their psychological conditions. Mothers begin to want to interact with their children, not showing symptoms of stress and anxiety. The family also understands the condition of the postpartum mother. The level of stress of postpartum mothers before assistance was found that experienced mild stress 5 people (41.67%) and moderate stress, namely 7 people (58.33%). After mentoring, it was found that 100% of the postpartum mothers were normal.